Epinephelus coioides Hsp27 negatively regulates innate immune response and apoptosis induced by Singapore grouper iridovirus (SGIV) infection. Issue 120 (January 2022) - Li, Pin-Hong; Cai, Yi-Jie; Zhu, Xiang-Long; Yang, Jia-Deng-Hui; Yang, Shi-Qi; Huang, Wei; Wei, Shi-Na; Zhou, Sheng; Wei, Jing-Guang; Qin, Qi-Wei; Sun, Hong-Yan
Abstract: Heat shock proteins (Hsps) are important for maintaining protein homeostasis and cell survival. In this study, Hsp27 of Epinephelus coioides, an economically important marine fish in China and Southeast Asian countries, was characterized. E. coioides Hsp27 contains the consered ACD_HspB1_like domain and three p38 MAPK phosphorylation sites, located at Thr-13, Thr-60 and Ser-167. E. coioides Hsp27 was distributed in both the cytoplasm and nucleus, its mRNA was detected in all 14 tissues examined, and its expression was up-regulated after challenge with Singapore grouper iridovirus (SGIV), an important E. coioides pathogen. Over-expression of E. coioides Hsp27 significantly upregulated the expressions of the key SGIV genes (VP19, LITAF, MCP, and ICP18), downgraded the expressions of the E. coioides immune factors (IRF3, IRF7, ISG15, and TRAF6) and proinflammatory factors (TNF-α, IL-8), downgraded the activation of nuclear factor kappa-B (NF-κB) and activator protein-1 (AP-1), and substantially inhibited the cell apoptosis induced by SGIV infection. These data illustrated that E. coioides Hsp27 might be involved in SGIV infection by negatively regulating the innate immune response. Highlights: Heat shock protein 27 (Hsp27) was characterized from Epinephelus coioides. E. coioides Hsp27 mRNA were detected in all tissues examined, and significantly up-regulated during SGIV infection. E. coioides Hsp27 can promote SGIV replication, and negatively regulates innate immune response. E. coioides Hsp27 could inhibit the SGIV-induced cells apoptosis.